Students’ Ability in Identifying Transitivity System: A Study at English Language Education Program of UNP - Fadrinasesa, Dinda; Fatimah, Sitti (Journal of English Language Teaching, 2024)
The purpose of this research is to know students’ ability and students’ difficulties in identifying transitivity system. The population of this research was all English Language Education Program of UNP in academic year 2021, while the sample of this research was K2 Class which consisted of 22 students. This research used descriptive with quantitative method and included two instruments: transitivity test and questionnaire. The transitivity test was used to know the students’ ability in identifying transitivity system while questionnaire was used to know students’ difficulties faced by them. The mean of student’ ability in identifying transitivity system was poor with score 47.72. In addition, students’ difficulties in identifying transitivity encountered that there were several significant challenges. The most difficulties that faced by the students were relational identifying process, mental process and verbal process. Difficulties in relational identifying process was difficulty in determining “role” “identity” or “meaning” with 86.3%. Difficulties in mental process were difficulty in determining verbs of feeling, thinking, and perceiving with 81.8%. Additionally, in verbal process, students had limited understanding of the function of Target with 77.2%.